Butlerian Theory of Performativity in Kartini: Princess of Java - Ria Saraswati; Engliana Engliana (Scope : Journal of English Language Teaching, 2023)
This research examines Kartini in Kartini: Princess of Java through the lens of Judith Butler’s concepts of vulnerability and gender performativity. Butler argues that cultural norms and power structures shape individuals’ gender identities and render them inherently vulnerable to external influences. By applying Butler concepts to the stories in Kartini: Princess of Java, the article asserts that the characters not only conform to gender norms to gain recognition but also face vulnerability due to her position within societal structures. This research carried out in a qualitative framework. The analysis explored how the character performed gender roles and the implications of her actions in the social realm. The findings show that Kartini’s performative acts involves breaking free from the normative scripts assigned to women of her time. She confronts gender expectations through her outspokenness, challenging practices like early marriages and polygamy that perpetuate inequality. Her advocacy for women's education is a performative act that aims to disrupt the conventional roles of women and to open new possibilities for their empowerment. This performative activism is intricately intertwined with Kartini's vulnerability. She shares her inner struggles, aspirations, and conflicts, transcending the boundaries set by her society. Her vulnerability becomes a catalyst for social change, inspiring other women to join her cause and challenge existing norms. Kartini's willingness to embrace her vulnerability demonstrates authenticity and sincerity, making her advocacy relatable and impactful.